Chylous fistula after right breast fibroadenoma resection: a case report - Liu, Haoxi; Liu, Liping; Yang, Xinhua (Frontiers in Surgery, 2024)
Chylous fistula is a common postoperative complication for the head and neck surgery, thoracic and upper gastrointestinal surgery, but it rarely happens after breast surgery. There are few reports of chylous fistula after breast benign tumor resection according to literature retrieval. To our acknowledgement, this is the first case report of chylous fistula after breast fibroadenoma resection.